Application of Carbon Capture and Utilization (CCU) in Oil and Gas Industry to Produce Microalgae-Based Biofuels with Solvent-Captured Method - Darwin Riyan Ramadhan; Asma Nadia; Alfira Maulidyah Rahmah (Indonesian Journal of Energy, 2023)
The production process in the oil and gas industry, which is a major demand, still plays a huge role in carbon emissions, especially in the refining process. The energy and industrial sectors are responsible for more than 75% of these global CO2 emissions. This condition is an important issue regarding the effort to reduce climate change due to these emissions by implementing CCU. This article aims to examine methods of carbon capture with chemical absorption by solvents and to compose a model diagram of carbon utilization with microalgae. An extensive literature search was conducted in accordance with the scoping review methodology and the PEO framework. Our search criteria were limited to article research within the last 5 years (2017–2021). Themes found from this review included the CCU method in general, carbon capture by solvent method, type of solvent used, advantages and disadvantages, and utilization of carbon in the gas and oil industries. CCU is a model that can be offered as an alternative to reduce CO2 emissions produced by industry. The scoping review result shows the best method for carbon capture is with monoethanolamine (MEA) solvent. The flue gas from post-combustion streams into the absorption column and the solvent is added. The carbon-rich solvent is regenerated by heat to produce a clean solvent to be reused in the capture cycle. Carbon that has been absorbed by the MEA in the form of gas will be channeled through pipes to the microalgae industry as utilization of captured carbon and then converted to biofuels. It was discovered that MEA is a cost-effective solvent, efficiently captures carbon, and can be used repeatedly. However, the amine emissions from MEA are considered hazardous. The conclusion is that MEA solvent has advantages and disadvantages. Further optimization research is needed to determine the preeminent capture and separation process. Thus, it is necessary to determine the best conditions for the use of captured carbon by microalgae.